Conserved TAAATG sequence at the transcriptional and translational initiation sites of vaccinia virus late genes deduced by structural and functional analysis of the HindIII H genome fragment. - Rosel, J L (1986)
The sequence of the 8,600-base-pair HindIII H fragment, located at the center of the vaccinia virus genome, was determined to analyze several late genes. Seven major complete open reading frames (ORFs) and two that started from or continued into adjacent DNA segments were identified. ORFs were closely spaced and present on both DNA strands. Some adjacent ORFs had oppositely oriented overlapping termination codons or contiguous stop and start codons. Nucleotide compositional analysis indicated that the A-T frequency was consistently lowest in the first codon position. The sizes of the polypeptides predicted from the DNA sequence were compared with those determined by polyacrylamide gel electrophoresis of cell-free translation products of mRNAs selected by hybridization to cloned single-stranded DNA segments or synthesized in vitro by bacteriophage T7 RNA polymerase. Six transcripts that initiated within the HindIII H DNA fragment were detected, and of these, four were synthesized only at late times, one was synthesized only early, and one was synthesized early and late. The sites on the genome corresponding to the 5' ends of the transcripts were located by high-resolution nuclease S1 analysis. For late genes, the transcriptional and translational initiation sites mapped within a few nucleotides of each other, and in each case the sequence TAAATGG occurred at the start of the ORF. The extremely short leader and the absence of A or G in the -3 position, relative to the first nucleotide of the initiation codon, distinguishes the majority of vaccinia virus late genes from eucaryotic and vaccinia virus early genes.